2005
DOI: 10.1093/brain/awh527
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic-like plasticity of the primary motor hand area is impaired in focal hand dystonia

Abstract: The excitability of inhibitory circuits in patients with writer's cramp is reduced at multiple levels within the sensorimotor system, including the primary motor hand area (M1). Although this may play a major role in the pathophysiology of writer's cramp, it is still unclear what factors may cause the imbalance between inhibition and excitation to arise. One possibility is that homeostatic mechanisms that keep cortical excitability within a normal physiological range are impaired. In eight patients with writer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
2
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(131 citation statements)
references
References 27 publications
7
117
2
5
Order By: Relevance
“…The enhanced modifiability of the R2 response in patients with BEB is consistent with an increasing body of research suggesting that focal task-specific dystonias of the hand result from aberrant sensorimotor plasticity (Berardelli et al, 1998;Hallett, 1998;Quartarone et al, 2003Quartarone et al, , 2005. In monkeys, rapid, repetitive, stereotypical movements in a learning context can actively degrade the cortical representations of sensory information that guide fine hand movements (Byl et al, 1996).…”
Section: Discussionsupporting
confidence: 78%
“…The enhanced modifiability of the R2 response in patients with BEB is consistent with an increasing body of research suggesting that focal task-specific dystonias of the hand result from aberrant sensorimotor plasticity (Berardelli et al, 1998;Hallett, 1998;Quartarone et al, 2003Quartarone et al, , 2005. In monkeys, rapid, repetitive, stereotypical movements in a learning context can actively degrade the cortical representations of sensory information that guide fine hand movements (Byl et al, 1996).…”
Section: Discussionsupporting
confidence: 78%
“…Dystonia is triggered or worsened by injury that increases long-term potentiation (LTP) in the cortex that corresponds to the injured limb. From an experimental point of view, dystonia is associated with an excessive response to several plasticity-inducing protocols, e.g., rTMS (Quartarone et al, 2005). These data support the hypothesis that in dystonia there is an increased tendency to form associations between inputs and outputs, which could lead to abnormal unwanted connections and subsequent impairment of motor control.…”
Section: Introductionsupporting
confidence: 70%
“…TBS after-effect was enhanced in dystonic patients but not in their symptomatic relatives (185). Moreover, in dystonic patients, cortical responses to 1Hz rTMS is unaffected by pre-conditionning with anodal TDCS contrarily to normal controls (179,181). In dystonia, there would be an increased tendency to form associations between sensory inputs and motor inputs which may lead to de-differentiation of motor representations in accordance with the theory of synaptic homeostatis (7,186,187).…”
Section: Plasticity In Dystonia: a Central Mechanismmentioning
confidence: 79%
“…In humans, the physiological basis of LTP and LTD is limited to TMS and transcranial direct current stimulation (TDCS) of the cerebral cortex (7). Two main techiques have been used to study plasticity at the cortical level: repetitive TMS (rTMS) with variable frequencies inducing either LTP or LTD (172,178) and paired-associative stimulation (PAS) combining electrical stimulation of a peripheral nerve and cortical TMS (172,179,180). It was shown that the sensorimotor cortex (SM) exhibited an exaggerated responsiveness to rTMS responding protocols (90,(181)(182)(183)(184).…”
Section: Plasticity In Dystonia: a Central Mechanismmentioning
confidence: 99%